Implementasi Asesmen Autentik Berbasis Kompetensi dalam Pembelajaran Abad Ke-21: Penelitian - Kalyana, Dyani; Hayatunnufus, Gina; Fauziah, Farrah Hany; Wijaya, Hari Rachmat; Haryani, Rini; Sudarmaji, Sudarmaji; Sumarmia, Sumarmia; Larashati, Larashati; Damayanti, Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Authentic assessment based on competency has become an essential component of 21st-century learning, as it enables comprehensive evaluation of students’ cognitive, affective, and psychomotor competencies. This study aims to analyze the implementation of authentic assessment through a literature review of 24 published articles examining its practices, effectiveness, and challenges across various educational levels. The analysis shows that authentic assessment positively contributes to student engagement, higher-order thinking skills (HOTS), and the development of collaboration, communication, creativity, and character. The assessment instruments developed in these studies are reported to be valid and reliable for measuring holistic competencies. However, several challenges persist, particularly regarding teachers’ ability to design rubrics, formulate performance indicators, and assess affective and psycho motor domains objectively. Limited time, administrative workload, and adaptation to online learning further hinder its implementation. This review highlights the need for strengthening teacher capacity, providing standardized assessment instruments, and ensuring policy support to optimize the sustainable application of authentic assessment in 21st-century learning.